Business Model Canvas : Vaclower D312 / Luqman Afiq Mohd Adnan - Mohd Adnan, Luqman Afiq (2020)
According to the BMC, this Vaclower D312 is a multifunctional product that can do wet/dry vacuum and also blow dust and debris. This will absolutely save customers’ spending because they do not have to spend more to buy three separate products to do all of the above tasks. Other than that, this product is also small in size and mobile in which will make it easier to be carried around anywhere. Most of the vacuum cleaners in the market are big in size and also heavy. The user needs to use more workforce just to carry the big and heavy vacuum cleaner. Thus, it will cause the user to experience exhaustion due to carrying the vacuum cleaner. With Vaclower D312, the user does not have to use more workforce to carry it around. In fact, the user can use the vaclower in a small space that limits movement when using the old version of multifunctional vacuum cleaner.